First report of systemic toxoplasmosis in a New Zealand sea lion (Phocarctos hookeri). Issue 1 (2nd January 2017) - Roe, WD; Michael, S; Fyfe, J; Burrows, E; Hunter, SA; Howe, L
Abstract: CASE HISTORY: A 1-year-old female New Zealand sea lion ( Phocarctos hookeri ) was intermittently observed in the Otago region of New Zealand over an 11-month period, always dragging her hind flippers. In December 2012 the sea lion was found dead, after a period of several days being observed to be harassed by male sea lions. PATHOLOGICAL FINDINGS: At gross postmortem examination the sea lion was in moderate body condition with signs of recent bite wounds and bruising. The lungs were dark and poorly inflated. Histological findings included meningoencephalomyelitis, radiculomyelitis of the cauda equina, myocarditis and myositis. Toxoplasmosis gondii organisms were detected histologically and following immunohistochemistry in the brain, spinal cord, spinal nerves and pelvic muscles. MOLECULAR BIOLOGY: Nested PCR analysis and sequencing confirmed the presence of T. gondii DNA in uterine and lung tissue. A variant type II T. gondii genotype was identified using multilocus PCR-restriction fragment length polymorphism analysis. DIAGNOSIS: Systemic toxoplasmosis. CLINICAL RELEVANCE: Infection with T. gondii involving the spinal cord and nerves was the likely cause of the paresis observed in this sea lion before death. Ultimately, death was attributed to crushing and asphyxiation by a male sea lion, presumably predisposed by impaired mobility. Diagnosis of toxoplasmosis in a New Zealand sea lion highlights the possibility that this disease could play a role in morbidity and mortality in this endangered species, particularly in the recently established mainland populations that are close to feline sources of T. gondii oocysts.